COMBINING THE DELAYED DIFFERENTIATION POLICY AND COMMON PARTS’ PARTIAL OUTSOURCING STRATEGY INTO A MULTI-ITEM FPR-BASED SYSTEM - Chiu, Singa Wang; Zhao, Zhong-Yun; Chiu, Tiffany; Chiu, Yuan-Shyi Peter (Journal of Applied Engineering Science, 2020)
This study investigates a multi-item finite production rate- (FPR-) based system incorporating a delayed product differentiation policy and common parts’ outsourcing strategy. A two-stage fabrication scheme is proposed, wherein, in stage one, all common parts of the end products (assuming they have a known completion rate as compared with the finished products) are partially produced in-house and partially supplied by an outside contractor with an extra unit outsourcing; in stage two, all end products are finished in sequence, under a rotation fabrication cycle time discipline. An explicit model is developed to clearly represent the proposed problem. Through the optimization technique, the optimal rotation cycle decision is obtained. Thus, diverse characteristics of this particular multi-item, FPR-based system with postponement and outsourcing strategies can now be revealed. As demonstrated by numerical illustrations, these characteristics include the (i) convexity of the system cost function, (ii) impact of common parts’ outsourcing strategy on the utilization, (iii) breakup of system cost components, (iv) combined impact of the outsourcing ratio and common parts’ completion rate on the system cost function, and (v) effect of the outsourcing ratio on optimal rotation cycle decision. Our decision-support-type system can facilitate production managers in achieving their goals of reducing orders’ response times and minimizing the overall system cost.